Pengukuran Kinerja Lingkungan Industri di Indonesia berdasarkan Standar Industri Hijau - Christiani, Agustina; Kristina, Helena Juliana; Rahayu, Priskila Christine (Jurnal Rekayasa Sistem Industri, 2017)
National industries need to anticipate the numerous environmental issues in international trade, in order to compete with other countries. Ministry of Industry Republic of Indonesia has responded that issue by putting green industry as an important part of Master Plan of National Industry Development 2015 â 2035. To encourage industry in implementing green industry principle, since 2010 Ministry of Indsutry has conducted Green Industry Award. Although each year, there is an increasing number of award receivers, but comparing with the total numbers of industries in Indonesia, the percentage of award receivers is so small. Therefore, this research is conducted to measure the environmental performance of several industries in Indonesia in order to know whether industries are ready to implement green industry standard. Data were collected in 6 manufacturing industries, based on the green industry self-assessment form released by ministry of industry. From the sixth industries which were evaluated, there are two industries that show low commitment to the environment because their scores are below 50. There is one industry categorized as green industry level 1 (score=56.5). Meanwhile there are two industries categorized as level 3 (score= 77.1 and 79.8) and one industry reached level 4 (score 82.1).Keywords: green industry,environment performance, self-assesment